2016
DOI: 10.1007/978-1-4939-6524-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs in Cancer

Abstract: It is believed that microRNAs have potential as circulating biomarkers of disease; however, successful clinical implementation remains a challenge. This chapter highlights broad variations in approaches to microRNA analysis where whole blood, serum and plasma have each been employed as viable sources. Further discrepancies in approaches are seen in endogenous controls and extraction methods utilized. This has resulted in contradictory publications, even when the same microRNA is targeted in the same disease se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…The other reasons may be due to different tissues that we tested and the different methods of detection. Recent miRNA profiling studies have indicated that circulating miRNAs hold great potential as stable blood-based markers for human cancers 13 , 14 . The identification of novel, reliable, minimally invasive breast cancer biomarkers in body fluids, such as serum and plasma, would represent a significant development in the clinical management of this complex disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other reasons may be due to different tissues that we tested and the different methods of detection. Recent miRNA profiling studies have indicated that circulating miRNAs hold great potential as stable blood-based markers for human cancers 13 , 14 . The identification of novel, reliable, minimally invasive breast cancer biomarkers in body fluids, such as serum and plasma, would represent a significant development in the clinical management of this complex disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the characteristic that miRNAs generally can be well-preserved in FFPE tissues, body fluids and other types of specimen 13 , 14 , they can provide clinically relevant information about cancer patients. Therefore, miRNA expression signatures have been identified as promising biomarkers with diagnostic and prognostic values in cancer treatment 15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, another study has shown that specific miRNAs may not consistently be detected among serum, plasma and whole blood, such as miR-504 and miR-138. Caution should be exercised in selecting the appropriate sample type if detection of specific circulating miRNAs is required [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…EVs encapsulate a plethora of potentially clinically relevant biomolecules, including microRNAs (miRNAs) [1], which have been at the forefront of breast cancer research in recent decades, with innumerable studies attempting to elucidate biomarker potential [13][14][15]. Despite initial promise, circulating miRNAs have yet to be implemented in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is multifactorial and includes broad variations in starting materials (whole blood, serum, or plasma) and extraction methods, and inconsistent use of endogenous controls [13]. As a result of this, the body of research on cancer-related miRNAs is contrasting, with conflicting results reported for the same miRNA being commonplace, even when evaluated in an identical disease setting [13]. Limiting the focus of interest to the miRNA contained in the EV fraction of blood alone may help to overcome these challenges.…”
Section: Introductionmentioning
confidence: 99%